Factores asociados a neuropatía periférica en diabéticos de 40 a 79 años, desde una perspectiva familiar. Loja 2016. - Godoy Chamba, Elisa Maribel (2017)
Mellitus Diabetes (MD) is one of the diseases with more socio sanitary impact, not only due to the higher prevalence but also because of the chronic complications that it produces, being the Periphery Diabetic Neuropathy the most frequent and earliest; it affects to the 60-70% of the patients; and, it is a risk factor for ulcer of lower limbs, the same that precede amputation until a 75%. The family, social group characterized by a common residence, economic cooperation and reproduction; it is being in constant transformation, so, at the presence of a disease, most of the patients and their related adapt adequately to the new situation, despite of the tensions and restructuration that it demands. The group is capable to reorganize, and strength ties. The objective of this investigation was to determinate risk and protection factors for the Peripheral Neuropathy apparition from a familiar perspective. The study was analytical in a sample of 500 people, of 40 to 79 years old, with MD2 Proven Diagnosis, giving their consent. The sources used were neuropathy detection questionnaire: The Michigan Neuropathy Screening Instrument (MNSI), depression, anxiety and stress test (DAS-21), familiar functionality FF-SIL questionnaire; also, Glycosylated Hemoglobin was measured. Diabetic Peripheral Neuropathy prevalence was about 56, 4%; The relationship with familiar functionality was not found significant; there was found significant association between age variables, depression, anxiety, stress, poorly controlled arterial pressure, lack of physical activity and altered glycosylated hemoglobin. The most significant risk factor was the evolution time since mellitus diabetes diagnosis. Keywords: glycosylated hemoglobin, associate factors, familiar functionality